Unnatural bedfellows? The sociolinguistic analysis of variation and language documentation. Issue 2 (3rd April 2019) - Meyerhoff, Miriam
ABSTRACT: Sociolinguistics and language documentation are both sub-fields of linguistics dealing with variation in natural language, but how they approach variation differs. This paper suggests that sociolinguistic studies of probabilistic variation can contribute not only to more thorough documentation of the structure of a lesser-known language, but also contribute to the advancement of linguistic theory and language change over time. Conversely, central concepts in sociolinguistics may need to be reconsidered when researchers begin to look beyond urban, monolingual communities of speakers. Two case studies are presented: the first case study of Bislama pronouns and subject agreement shows that documenting the structure of a lesser-studied language can help elucidate what might have happened in the past. It also shows how an analysis of variation can address outstanding questions about the fundamental linguistic structure of an under-documented language and the ways that variation feeds into grammaticalisation. The second case study presents an analysis of another variable in Bislama that problematises the alleged simplicity of creole languages, and proposes a general principle of transformation of constraints in situations of language contact. The paper suggests that, although the combination of sociolinguistics and language documentation may always be uneasy, they can make surprisingly congenial bedfellows.